Testes de Função da Trompa de Eustáquio: avaliação prospetiva da acuidade diagnóstica - Lima, António Fontes; Carvalho Moreira, Filipa; Sousa Menezes, Ana; Azevedo, Catia; Costa, Isabel; Milhazes Mar, Fernando; Dias, Luís (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2020)
Eustachian tube dysfunction (ETD) may relate to otologic disorders of variable severity. Its diagnosis is based on symptoms and signs, being the usefulness of eustachian tube function tests undetermined. However, patients selection to procedures such as ET dilation should be dependent on objective and reproductive exams. The objective of this study is to assess the diagnostic accuracy and correlation between different exams. Methods and methodology: two groups of patients were selected: one convenience sample of patients with clinical diagnosis compatible with obstructive ETD (based on symptoms and physical exam signs); one convenience sample of control patients (without symptoms or signs). The sample of patients with obstructive ETD was validated by 3 Otorhinolaryngologists, and only the ones who gathered consensus of the three were included. All the patients were prospectively evaluated with 3 tests: a patient-reported outcome measure, validated in Portuguese – Eustachian Tube Dysfunction Questionnaire-7 (ETDQ-7), tympanometry T; and tubomanometry (TMM). Sensitivity (Se), specificity (Sp), positive predictive value (PPV) and negative predictive value (NPV) were calculated. Pearson correlation was used to test the correlation between them. Receiver-operating characteristic (ROC) curves were created and the area-under the curve (AUC) was used to compare between them. Statistical analysis was performed with macOS, and a p-value < 0,05 was used to reject the null hypothesis. Results: the group of obstructive ETD was comprised by 36 patients; the control group by 27 patients. ETDQ-7 had a high Se (94,4%), but low Sp (40,7%); the opposite was verified regarding tympanometry (Se of 61,1% and Es of 92,6%); TMM had a high Se and Sp, of 91,7% and 67,7%, respectively. Despite a statistically significant correlation between the three used tests, they were weak, except for tympanometry and TMM, that was moderate. The AUC of TMM was the highest of the three (0,8 ± 0,06), followed by tympanometry (0,71 ± 0,07). Discussion and conclusion: our results are compatible with the most recent literature, that means that no test or exam is sufficient when used alone. If, on one hand, all the tests can be useful, when isolated, tympanometry is insufficient, ETDQ-7 may overestimate, and TMM is the most accurate of the three.